Findings on the Relationship Between Intestinal Microbiome and Vasculitis - Sun, Boyuan; He, Xin; Zhang, Wen (Frontiers in Cellular and Infection Microbiology, 2022)
The microbiome has been implicated in small-, medium-, large-, and variable-vessel vasculitis. Dysbiosis can frequently be found in vasculitis patients with altered microbial diversity and abundance, compared with those with other diseases and healthy controls. Dominant bacteria discovered in different studies vary greatly, but in general, the intestinal microbiome in vasculitis patients tends to contain more pathogenic and less beneficial bacteria. Improvement or resolution of dysbiosis has been observed after treatment in a few longitudinal studies. In addition, some molecular changes in intestinal permeability and immune response have been found in animal models of vasculitis diseases.